ANALISA KESELARASAN PROGRAM CORPORATE SOSIAL RESPONSIBILITY (CSR) PERUSAHAAN YANG BEROPERASI DI KABUPATEN INDRAGIRI HILIR DENGAN SUSTAINABLE DEVELOPMENT GOALS (SDGS) - M. Gasali. M , Syafrizal Thaher (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2018)
Corporate Social Responsibility (CSR) is the commitment of company to contribute in sustainable economic development which focused on balance among the concern of economic aspect, social and environment. The design of this research is qualitative to view the consistent of corporate CSR program which is operated in Kabupaten Indragiri Hilir through the goverment program on Sustainable Development Goals (SDGs). Based on this research, it can be concluded that the CSR of corporate which is operated in Indragiri Hilir supported the implementation of SDGs by 18 SDGs indicators including social pillar, economic pillar and environment pillar.